2021
DOI: 10.1002/cbdv.202100065
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Liver Dysfunction, Oxidative Stress, and Inflammation Underlines the Protective Effects of Polysaccharides from Cordyceps cicadae on High Sugar/High Fat Diet‐Induced Metabolic Syndrome in Rats

Abstract: This study investigated the protective effects of two polysaccharides (CPA‐1 and CPB‐2) from Cordyceps cicadae against high fructose/high fat diet (HF/HFD) induced obesity and metabolic disorders in rats. Rats were either fed with normal diet or HF/HFD and treated with CPA‐1 and CPB‐2 (100 and 300 mg/kg) for 11 weeks. Administration of CPA‐1 and CPB‐2 significantly and dose dependently reduced body and liver weight, insulin and glucose tolerance, serum insulin and glucose levels. Furthermore, serum and hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…TCM has the advantage of being multi-targeted. Recently, C. cicadae has been shown to possess a wide range of pharmacological activities in the kidney, which include renal interstitial fibrosis, anti-apoptosis, anti-inflammatory, antiaging, antioxidative stress, and immunoregulatory effects ( Xie et al, 2019 ; Yang et al, 2020 ; Zhang X. et al, 2021 ; Chyau et al, 2021 ). In our study, C. cicadae displayed an advantage for reducing renal fibrosis compared with RES.…”
Section: Discussionmentioning
confidence: 99%
“…TCM has the advantage of being multi-targeted. Recently, C. cicadae has been shown to possess a wide range of pharmacological activities in the kidney, which include renal interstitial fibrosis, anti-apoptosis, anti-inflammatory, antiaging, antioxidative stress, and immunoregulatory effects ( Xie et al, 2019 ; Yang et al, 2020 ; Zhang X. et al, 2021 ; Chyau et al, 2021 ). In our study, C. cicadae displayed an advantage for reducing renal fibrosis compared with RES.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic antioxidant balance was compromised both in female and male offspring since the antioxidant activity of SOD was decreased ( Figure 5 ). Numerous authors have also found a decrease in SOD activity in adult rats and humans with MetS [ 150 , 151 , 152 ]. In this context, Liu et al studied the association between SOD activity and MetS progression, observing that the activity of this enzyme showed a linear descending trend according to the sequential progression of the MetS different components, such as impaired insulin sensitivity and β-cell dysfunction [ 153 ].…”
Section: Selenium Mets Programmingmentioning
confidence: 99%
“…Astragalus polysaccharides also attenuated hepatic steatosis by regulating gut flora and host metabolism [25] . Polysaccharides from cordyceps cicadae inhibited liver dysfunction, oxidative stress, and inflammation in rats with metabolic syndrome induced by HFD [26] . Therefore, developing strategies to improve intestinal flora disorders and gut barrier function is a potential strategy to prevent and treat NAFLD [12] …”
Section: Introductionmentioning
confidence: 99%